All Strings Attached : Migrant Poverty, Legal Status and the Welfare State: conditionality of legal status and the determination of third-country national poverty in western Europe - Corrigan, Owen (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2012)
The thesis sets out to account for variations in migrant poverty across states in Western Europe, specifically the poverty of third-country nationals (TCNs). The intersecting literatures on the welfare state, migration and migrant legal status make clear that the position of TCNs is qualitatively different from natives and from other types of migrant. Extant accounts such as welfare regime theory fail to explicate cross-national variations in poverty when TCNs are the unit of analysis. For TCNs, full and secure access to the welfare state is contingent on holding long-term residency (LTR) status and transition to a more secure legal status is subject to a process governed by conditionality. Extant literature has neglected to account for tliis process. The thesis asks what role conditionality of legal stams can play in explaining TCN poverty outcomes and what this means for extant understandings of welfare in Europe. States impose conditions on moving between legal statuses, and the stringency of these conditions varies cross-nationally in a manner held to be an explanatory factor capable of accounting for cross-national variation in TCN poverty outcomes. Where rights-granting legal status is difficult to attain migrants will subsist in insecure life positions without recourse to the supports of the welfare state. The employment-contingency of presence in the state means that disadvantageous labour market attachments may be tolerated so as not to jeopardise the right to reside in the host country. The theoretical framework thus conceptualises conditionality as impacting on the poverty of TCNs in interaction with features of the work-welfare nexus. The generosity of the welfare state will act to reduce poverty, but this effect will be moderated by the difficulty of attaining the legal status granting access to welfare protections.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin